Improving Students’ Opinoning Ability and Learning Outcomes Through Problem-Based Learning in VIII grade - Heri Ginanjar (Universitas of Muhammadiyah Makassar, 2023)
This research aims to increase student activity in expressing opinions and student learning outcomes in PPKN subjects by implementing the problem-based learning (PBL) learning model. The type of research used is PTK. The research subjects were class VIII SMP IT Qur'an Al Fath, Sukabumi City students. Data collection techniques use tests, observation data, and activity assessment rubrics. The data analysis techniques used are quantitative and qualitative descriptive. The results of research on learning activity in the pre-cycle were (35.13%) 23 inactive students increased in cycle I to (36.73%) 11 quite active and in cycle II increased to (97%) 33 active students. Meanwhile, the pre-cycle learning results showed completeness of (41%) 15 students then increased in cycle 1 to (54%) 20 students and (81%) 30 students in cycle II. In this way, the hypothesis proposed by the researcher has been proven to be true, so it can be concluded that the application of the Problem-based learning (PBL) learning model can increase student activity in expressing opinions and learning outcomes for VIII grade SMP IT Qur'an Al Fath, Sukabumi City. Therefore, applying the problem-based learning (PBL) learning model can increase the activity and learning outcomes of class VIII students at SMP IT Qur'an Al Fath, Sukabumi City.